Characteristics of downward and upward longwave radiation at athalassa, an inland location of the island of Cyprus - Pashiardis, Stelios; Kalogirou, Soteris A. (My University, 2021)
In this study, two years of hourly longwave downward and upward irradiance measurements at Athalassa, an inland location, are used to analyze and compare them. A detailed quality control process was followed according to the suggested tests proposed by the Baseline Surface Radiation Network (BSRN) group. The criteria involved are based on physically possible, extremely rare and climatological limits. Furthermore, comparison tests were also applied between the two longwave components as well as with air and ground surface temperatures. Additionally, time consistency and persistency tests were applied. All the suspect data were excluded from the analysis. The frequency distribution of downward longwave irradiances, the data showed that it follows a normal distribution function, while the upward longwave follows an almost normal distribution but with a long positive tail. The annual mean daily downward longwave irradiation is 27.3 MJ m−2 and the annual mean daily upward longwave irradiation is 37.8 MJ m−2. The net longwave irradiation is always negative ranging from −5.9 to −12.1 MJ/m2. Various models were tested to estimate daylight and all day downward and upward longwave irradiances under clear-sky and all-sky conditions. For the comparison of measured and estimated values the root-mean-square errors and linear regression correlations have been used. The results of this comparison showed that Idso’s and Brunt’s models perform well, and they can be used to estimate downward longwave irradiance under clear-sky conditions. Furthermore, both models were extended to estimate the daylight downward longwave irradiance under all-sky conditions by taking into account the ratio of global to the clear-sky global solar irradiance. In this case, the RMSE of the local calibrated coefficients scheme of Idso’s model was 30.6 W m−2, while Brunt’s model showed slightly lower value (29.0 W m−2).
Keywords: Downward longwave radiation; Modeling; Net longwave radiation; Quality control; Statistical analysis; Upward longwave radiation